Chicago Day Waltz - George Valisi::::::::: (Valisi Bros.)
Piano score, 4 p. Cover title: Chicago Day waltz, October 9th, 1893. At head of title on cover: Dedicated to Lena Burton Clarke, by kind permission. Chairman, Committee on Music, Board of Lady Managers. Also on cover is a lithograph in color of a birds-eye view of the Grand Basin and Administration Building, Lithograph by Orcutt Co., Chicago On p.1: Attendance 716,881.